2018
DOI: 10.1172/jci98012
|View full text |Cite
|
Sign up to set email alerts
|

A controlled human malaria infection model enabling evaluation of transmission-blocking interventions

Abstract: BACKGROUND. Drugs and vaccines that can interrupt the transmission of Plasmodium falciparum will be important for malaria control and elimination. However, models for early clinical evaluation of candidate transmission-blocking interventions are currently unavailable. Here, we describe a new model for evaluating malaria transmission from humans to Anopheles mosquitoes using controlled human malaria infection (CHMI).METHODS. Seventeen healthy malaria-naive volunteers underwent CHMI by intravenous inoculation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
153
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(169 citation statements)
references
References 36 publications
15
153
1
Order By: Relevance
“…Total gametocyte density, quantified in venous blood by quantitative reverse transcriptase PCR (qRT-PCR) targeting female-specific Pfs25 mRNA and male-specific Pfmget mRNA (29), was positively associated with the proportion of mosquitoes that became infected following direct skin feeding (Spearman ρ=0.415, p=0.0204) or membrane feeding (Spearman ρ=0.596, p = 0.0004) (Figure 1A). The proportion of infected mosquitoes was higher by direct skin feeding as compared to membrane feeding assays (odds ratio 2.01; 95% CI 1.21 – 3.33, p = 0.007), in line with previous studies (9, 10, 30). The medium number of oocysts was 4 (IQR 2-7.5; maximum 38) for mosquitoes that became infected after feeding directly on the skin and 2 (IQR 1-5; maximum 24) for mosquitoes that became infected after feeding on venous blood through a membrane feeder.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Total gametocyte density, quantified in venous blood by quantitative reverse transcriptase PCR (qRT-PCR) targeting female-specific Pfs25 mRNA and male-specific Pfmget mRNA (29), was positively associated with the proportion of mosquitoes that became infected following direct skin feeding (Spearman ρ=0.415, p=0.0204) or membrane feeding (Spearman ρ=0.596, p = 0.0004) (Figure 1A). The proportion of infected mosquitoes was higher by direct skin feeding as compared to membrane feeding assays (odds ratio 2.01; 95% CI 1.21 – 3.33, p = 0.007), in line with previous studies (9, 10, 30). The medium number of oocysts was 4 (IQR 2-7.5; maximum 38) for mosquitoes that became infected after feeding directly on the skin and 2 (IQR 1-5; maximum 24) for mosquitoes that became infected after feeding on venous blood through a membrane feeder.…”
Section: Resultssupporting
confidence: 90%
“…Again, we observed no evidence for higher concentrations of gametocytes in mosquitoes that fed directly on the skin of gametocyte donors compared to venous blood and observed a very strong association between gametocyte fractions from the different blood compartments. There must therefore be an alternative explanation for the higher infection rates that we, in line with other studies (9, 10), observed in direct skin feeding experiments compared to membrane feeding experiments using venous blood. Gametocyte activation may occur following phlebotomy and may reduce infection rates observed following membrane feeding.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our observation that after adjusting for gametocyte density, the risk of mosquito infection was lower in incident infections suggests that gametocytes arising in the incident cohort were less mature at the time of feeding. The requirement for gametocyte maturation following release into the circulation would be in line with earlier in vitro observations that morphologically mature gametocytes may require several days of maturation to reach peak infectivity 45 and with findings in controlled human infections where infectivity is only observed several days after gametocyte densities plateau 46 .…”
Section: Discussionsupporting
confidence: 83%